Hubungan Pengetahuan dan Sikap Ibu Dengan Upaya Penanganan Stunting Pada Anak di Wilayah Kerja Puskesmas Cireunghas - Winda Herawati; Hendri Hadiyanto; Hadi Abdillah (Jurnal Ventilator, 2024)
Stunting is a chronic nutritional problem caused by lack of nutritional intake over a long period of time, generally caused by food intake that does not meet nutritional needs, causing stunted growth in children. In other words, the child's height by that standard is less. Therefore, stunting can lead to an increased risk of illness, death, suboptimal brain development, and decreased mental development. One of the factors that can cause children to experience stunting is lack of knowledge or errors in providing nutritious food needed by children. Objective: to determine the relationship between knowledge and attitudes of mothers in efforts to handle stunting in children in the work area of the Cireunghas Health Center. Method: This research design uses a cross sectional approach. The sample size in this study was 69 people. The sampling technique used in this study is purposive sampling. Data analysis using chi-square test. Result: Based on the results of the chi-square statistical test, the resulting P value is 0.000 < 0.05. Conclusion: it can be concluded that there is a relationship between knowledge and mothers' attitudes in efforts to handle stunting in children in the Cireunghas Health Center Work Area. Suggestion: Further research is needed to look for other factors that influence the mother's level of knowledge and the relationship between these factors and the mother's level of knowledge.